Literature Review: The Implementation of Internal Controls in Fraud Prevention For The Banking Sector - Cahaya Putra, Vicky Dzaky; Djajadikerta, Hamfri; Setiawan, Amelia (Economic Reviews Journal, 2024)
Corrupt practices are one of the most common occurrences in the public sector. Corruption is usually prevented by management by establishing policies, systems and procedures. These are designed to ensure that the board, management and other employees of the company have taken the necessary measures to build confidence in their abilities. This is achieved by implementing internal controls. The aim of this research is to explain how internal controls are implemented to prevent banking crises. The research was conducted through literature studies, collecting journals and literature books on implementing internal controls with a focus on accident prevention. Based on the study results, it is clear that the introduction of internal control in the banking system enables research on comprehensive compensation prevention.